Retention and Selectivity of the Nalidixic Acid and Enoxacin by Hydrophilic Interaction Liquid Chromatography on Various Polar Columns with Different Chain Lengths - A. Al-phalahy, Bashaer; Radi Karabat, Raad; Amer Waheb, Ali; J. Mohammed, Mustafa; Saad Rasheed, Ashraf (Al-Nahrain Journal of Science, 2025)
This research aims to provide a comprehensive view of the separation mechanisms of HILIC stationary phases in various applications. This study was conducted to understand the retention behavior of nalidixic acid and enoxacin, to show the effect of alkyl chain length on their selectivity, and to develop a simple and sensitive HILIC method for their determination in pharmaceutical formulations. Two lab-made columns (ZIC-HILIC-1 and ZIC-HILIC-3) were used to examine the retention behavior of nalidixic acid and Enoxacin. The retention mechanism in this research was studied by investigating the effect of parameters that affect the selectivity of the separation, which include (acetonitrile content, pH, and buffer concentration). The zwitterionic columns are characterized by their different alkyl spacer chain length, which have been employed to examine the retention behavior of select drugs. The eluent consists of acetonitrile: 10mM acetate buffer (90:10 v/v, pH 4.75) equipped with a UV detector set at 220nm, at a flow rate of 0.75 mL/min. This research developed a ZIC-HILIC method to determine nalidixic acid and enoxacin in pharmaceutical formulations. The technique exhibited linearity in the concentration range (0.1– 6 μg/mL) and 0.1-12 μg/mL for nalidixic acid and Enoxacin, respectively. LOD is 0.070 and 0.04 μg/mL for nalidixic acid, and LOD is 0.080 and 0.060 μg/mL for enoxacin in ZIC-HILIC-1 and ZIC-HILIC-3 columns, respectively.